5-hydroxytryptamine measurement using paired pulse voltammetry - Kim, Suh Young; Oh, Yoon Bae; Shin, Ho Jin; Kim, Do Hyung; Kim, In Young; Bennet, Kevin; Lee, Kendall H.; Jang, Dong Pyo (Biomedical engineering letters, 2013)
Purpose Although paired-pulse voltammetry (PPV) has significantly reduced the effects of confounding factors such as pH changes, its appliance has been limited to triangular waveforms. Here, we extend PPV to N-waveform, known to be effective in differentiating serotonin (5-HT) from other analytes. Methods Unlike previous PPV that employs a triangular binary waveform with a specified time gap between the comprising pulses, this study experiments PPV with Nwaveform. N-waveform, the most conventional waveform for detecting 5-HT, sweeps from 0.2 V to 1.0 V to −1.0 V and back to 0.2 V at a sweep rate of 1000 V/s, while the electrode is held at a holding potential of +0.2 V between the voltammetric pulses. After experimenting with various gap times (2 ms, 10 ms, 30 ms, and 45 ms), N-shape PPV was optimized to the parameter of 100 ms repetition time (2 Hz) and 2 ms gap time that displayed the highest sensitivity. 5-HT measurement was performed with a carbon fiber microelectrode placed in the flow cell. PPV data was collected with the Wireless Instantaneous Neurochemical Concentration Sensing System. Results At the optimized parameter, the oxidation peak in secondary pulse of N-waveform PPV recorded about 68% of the peak of the primary pulse. In addition, the fitting of peak currents in primary, secondary, and primary-secondary in Nshape PPV in relation to the concentration level between 0.25 μM to 2 μM displayed high reliability (R-squared values = 0.9823, 0.9895, 0.9914, respectively). When 5-HT 3 μM and 0.1 ΔpH is mixed, the 10 nA artifact created by 0.1 ΔpH in P-S voltammogram was almost completely removed while the oxidative peak by 5-HT was detected. Conclusions These results demonstrate that N-shape PPV will enable more accurate measures of real-time serotonin changes, especially in complex environment.